Mediating God"s relationality? A trinitarian perichoretic critique of the reliance on anointed objects in African neo-Pentecostalism - Banda, Collium (HTS teologiese studies, 2020)
This article uses the perichoretic nature of the Trinity to evaluate the reliance on anointed objects as instruments of connecting with God amongst African neo-Pentecostal Christians. The article answers the question: from a perspective of the relationality of God, how can we evaluate the African neo-Pentecostal reliance on anointed objects to connect with God? The aim is to show that the perichoretic nature of the Trinity demands that a direct relationship with the Godhead be possible without the intermediary and impersonalising use of anointed objects. The use of anointed objects to connect with God impersonalises him and undermines his relationality, as depicted in his perichoretic triune nature. The significance of the article lies in calling for African neo-Pentecostals to inform their quest for an intimate connection with God by a critical understanding of his perichoretic trinitarian communal ontology.